Gravity-driven deepwater fold-and-thrust belts as Critical Coulomb Wedges: Model limitations and the role of friction vs. fluid pressure. (December 2021) - Tesei, T.; Cruciani, F.; Barchi, M.R.
Abstract: Gravity-driven Deepwater Fold-and-thrust Belts (GDFB) are the result of gravitational collapse of the sedimentary pile along the continental shelf. These systems can be described in the framework of the Critical Coulomb Wedge (CCW) mechanics to infer their mechanical properties and hydrological conditions. However, not all GDFB can be considered as critical wedges and their mechanical/hydrological parameters should be critically assessed. GDFB driven by gravity spreading and detached onto brittle overpressured shales are the most suitable systems to be modeled via the original CCW theory. In addition, the self-limiting mechanism of gravitational collapse implies that GDFB can reach the critical state only during limited time intervals (in some cases less than ∼10 Myr), in the presence of large sedimentary loads and shortening rates higher than 1.5–2 mm/yr. We present a compilation of GDFB that most likely represent examples of critical tapers, almost exclusively located downdip of large deltas. We then analyze several analytical solutions to the CCW equation, constrained by laboratory and geophysical data, to discuss the role of material friction and fluid pressures in GDFB. Low friction and moderate fluid overpressure localized in the basal detachment are both essential to explain the observed shape of GDFB. Frictional and overpressure discontinuities between detachment and the overlying wedge are likely to be maintained in GDFB. Highlights: Critical Coulomb wedges is appropriate for some gravity-driven tectonic wedges. Gravity-driven wedges are only episodically at the critical state. CCW is best applied to wedges dominated by gravity spreading with shale detachments. Lithostatic fluid overpressure is not necessary to model gravity-driven wedges. A combination of low friction and moderate overpressure in gravity-driven wedges.